Outplacement – An employment safety tool but not for everyone. The relationship between job insecurity, new job opportunities and outplacement implementation - Jerzy Kaźmierczyk; Anna Tarasova; Elena Andrianova (Cogent Business & Management, 2020)
This article explores outplacement models typical for understanding the roles of job insecurity and the subjective perception of opportunities to find a new job. This study aims to validate the following hypothesis: people who are covered by outplacement systems in a workplace usually feel that they have both a good opportunity to find a job and have low job insecurity. Outplacement was defined according to a matrix of job insecurity and the possibility of finding a job. This comparative study is the first one that investigates the differences in outplacement and was carried out taking into account job insecurity and job opportunities. The Job Opportunity Index was almost the same in Russia and Poland but the Job Insecurity Index in Poland was higher than in Russia. 51% of Russian bankers and 29% of Polish bankers indicated that they could count on outplacement services to help them. The hypothesis was not confirmed in Poland as it was in Russia. The hypothesis of this study is supported by empirical research carried out on a sample of 2324 bank employees in Poland and in the Russian Federation. Factor analysis, discriminant analysis, the Mann-Whitney test and the Wilks' Lambda test were used.
Keywords: 650; outplacement; job insecurity; job opportunities; bank